Gut Microbiota in Human Immunodeficiency Virus Infection - Rudi Wisaksana; Guntur Darmawan; Nenny Agustanti; Dolvy Girawan (The Indonesian Society for Digestive Endoscopy, 2019)
Human microbiota, majority presents in human gastrointestinal tract, plays crucial role in body physiological functions, such as immune system. Human immunodeficiency virus (HIV) infection impairs gut barrier and alter the microbiota ecosystem, called dysbiosis. Different phase of HIV infection demonstrates different composition of gut microbiota. Antiretroviral treatment might improve the CD4 level, however, it inconsistently restore the gut ecosystem. Some studies in prebiotic and probiotic revealed the potential effect in reducing inflammation and restoring gut microbiota.